Aplikasi Pupuk Organik Cair dan N, P, K Terhadap C-Organik, N-Total, Serapan N Serta Hasil Padi Sawah (Oryza sativa L.) Pada Inceptisol Asal Jatinangor - Rija Sudirja; Maya Damayani; Eso Solihin; Wulan Sri Damayanti (Soilrens, 2019)
Rice is one of the staples of Indonesian society. Development of rice cultivation can be carried out on Inceptisol soils. This land has a wide distribution of around 70.52 million, but it has an unfavorable fertility rate so fertilization is needed in order to increase fertility and yield of lowland rice. This study aims to determine the effect of a combination of liquid organic fertilizer and N, P, K fertilizer on C-Organic, N-Total, N uptake and Yield (Oryza Sativa L.) on Inceptisol from Jatinangor. The experiment was held on March 2019 until July 2019 at Ciparanje Experimental Field and Laboratory Soil Chemistry and Plant Nutrition, Faculty of Agriculture, Padjadjran University, Jatinangor, Sumedang. The experimental design was Randomized Block Design with ten treatments and three replications. The result of study showed that the combination of liquid organic fertilizer and N, P, K is affected on organic C, total N, N uptake and rice yield. The application of one liquid organik fertilizer and ¾ N, P, K gave the best rice yield of 8,55 kg/plot or equal to 6,84 ton/ha.